Low Prevalence of VRE Gastrointestinal Colonization of Hospitalized Patients in Manitoba Tertiary Care and Community Hospitals - George G Zhanel; Godfrey KM Harding; Stuart Rosser; Daryl J Hoban; James A Karlowsky; Michelle Alfa; Amin Kabani; John Embil; Alfred Gin; Trevor Williams; Lindsay E Nicolle (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the prevalence of vancomycin-resistant enterococci (VRE) bowel colonization in hospitalized patients in Manitoba who had stool specimens collected for Clostridium difficile toxin and/or culture testing.